Studies on bacterial soft-rot of onion in the western parts of Libya - ABUGHNIA, A.; ADAM, F. S. (The Libyan Journal of Agriculture, 2023)
he disease incidence of bacterial soft-rot of onion was the highest in Tripoli followed by El-Zawia, Ameria, Benghashir and Azizia, respectively. The onion cultivar Texas Yellow Grano 502 was more susceptible to infection than Red D-amposta. Two pathogenic bacteria were isolated from diseased onion bulbs, and were identified as Pseudomonas cepacia (Burkh.) and Erwinia cartovora (Jones). Each bacterium caused rotting of onion cultivars. Inoculation with a mixture of both bacteria showed an increased pathogenic effect.